2017
DOI: 10.1111/jfbc.12412
|View full text |Cite
|
Sign up to set email alerts
|

Biocalcium powder from precooked skipjack tuna bone: Production and its characteristics

Abstract: Biocalcium (BC) powder from the bones of precooked skipjack tuna was produced and characterized, compared to calcined bone (CB) powder. Higher calcium (40.35%) and phosphorous (15.28%) contents were found in the CB powder, compared to BC powder (26.91 and 12.63%, respectively). Nevertheless, similar Ca/P ratio was observed (1.62–1.65). Mean particle sizes of both powders were 17.07–20.29 µm. BC powder had higher b* (yellowness) with slightly lower L* (lightness) values than the CB counterpart (p < .05). Both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 28 publications
(47 reference statements)
4
45
0
2
Order By: Relevance
“…Percentage of ash content in HAp-1 (98.24%) was higher compared to RB (50.98%) probably due to the high composition of materials such as protein and lipid. This finding was in alignment with the previous study by Benjakul et al (2017), who found that the amount of ash content in the calcined bone of skipjack tuna is 99.75% due to the high amount of organic matter such as fat and protein. The ash content in fish bone is normally more than 40% depending on species (Toppe et al, 2007).…”
Section: Proximate Analysissupporting
confidence: 93%
“…Percentage of ash content in HAp-1 (98.24%) was higher compared to RB (50.98%) probably due to the high composition of materials such as protein and lipid. This finding was in alignment with the previous study by Benjakul et al (2017), who found that the amount of ash content in the calcined bone of skipjack tuna is 99.75% due to the high amount of organic matter such as fat and protein. The ash content in fish bone is normally more than 40% depending on species (Toppe et al, 2007).…”
Section: Proximate Analysissupporting
confidence: 93%
“…Fourier‐transform infrared spectroscopy revealed the presence of hydroxyproline and protein by amide I, II, and III peaks detection (Benjakul et al., 2017). Furthermore, BC showed higher bioavailability of Ca in the in vitro‐simulated gastrointestinal tract system, mainly due to the presence of collagen (Benjakul et al., 2017). Tilapia fish ( O. niloticus ) scales were used to prepare tilapia scale PH (TSPH) using commercial proteases (Lu et al., 2016).…”
Section: Biological Activities Of Fph (In Vitro Studies)mentioning
confidence: 99%
“…Fish bone is another by-product that can serve as a raw material for the production of high value-added compounds that can be used in various sectors including agrochemical, biomedical, food, and pharmaceutical industries [23]. Fish bone is considered as one of the potential biological sources to produce calcium phosphates [23,24]. Fish bone can be applied to boost nutritional characteristics in seasoning powder [25].…”
Section: Fish-processing By-productsmentioning
confidence: 99%
“…Additionally, fish bone is the source of hydroxyapatite (HA) known as (Ca 2+ ) 10Àx (H 3 O + ) 2Àx (PO 4 3À ) 6 (OH À ) 2 . Those bones could be converted to biocalcium (BC) powder, which is derived from bio-mineralized or a naturally produced resource [24].…”
Section: Fish Bonementioning
confidence: 99%